Manajemen Pengurangan Resiko Bencana Berbasis Komunitas: Community Based Disaster Risk Reduction Management - Nurcahyo, Mugi; Setyawan, Agus; Ansori, Teguh (Institut Agama Islam Sunan Giri Ponorogo, 2022)
The background of this study states that in a community environment even though the majority of the population is Muslim and as social beings, it cannot be used as a guarantee that the community has awareness of the values ​​contained in religion or awareness in participating in disaster management, and in participating in disaster management. Environmental welfare action. The environmental community in Krajan Hamlet, Baosan Lor Village, Ngrayun District spends a lot of time earning a living and working. The impact that occurs is that society is increasingly focused on worldly so that people are negligent with religious values ​​and as social beings. In this case, the awareness of religious leaders or community leaders in the environment in the Krajan Hamlet, Baosan Lor Village, Ngrayun District has an important role as a driving force and embracing in increasing religious awareness as well as making people aware of social actions for disaster management for environmental welfare. With the existence of communities and organizations that exist or are starting to form and move in this place, it is necessary to have management of the role of religious leaders, and driving figures in embracing the community. Because the purpose of the role of religious leaders and driving figures here is to be able to bully the community in building a peaceful, religious, and peaceful environment. Based on data analysis, this research uses a qualitative approach, namely research conducted by observing and analyzing it using scientific logic. With data collection techniques carried out by researchers including observation, documentation and in-depth interviews with informants who are considered to have a conferhensive understanding of information related to the research topic being carried out.